Clinical Utility of Interleukins in Sepsis-Associated Acute Kidney Injury: Current Evidence and Future Perspectives - Khaled Mohammed Youssef , Ahmed Noaman , Yasser Abdelmonem Abdelsalam Hindy , Ahmed Abdulsaboor Mohamed and Usama Ragab (Cuestiones de Fisioterapia, 2024)
Background: Sepsis-associated acute kidney injury (SA-AKI) is one of the most frequent and devastating complications of sepsis, substantially increasing morbidity, mortality, length of intensive care unit stay, and long-term risk of chronic kidney disease. Despite advances in supportive care, early diagnosis and accurate risk stratification remain challenging because conventional biomarkers, including serum creatinine and urine output, often fail to detect renal injury during